Fracture simulation of fiber reinforced composite panels with holes - Adesola Ademiloye (Composite Structures, 2025)
Fiber reinforced composite (FRC) with holes have broad applications in various fields. In this study, the influence of fiber orientation and hole distribution on the fracture behavior of FRC was investigated. A phase-field modeling was established to simulate the fracture process of the composite, and the mechanical performance of unidirectional fiber reinforced composite and woven fiber reinforced composite were analyzed, respectively. Our numerical results showed that fiber orientation and hole distribution have a significant impact on the fracture behavior of FRC. We observed that aligning the fibers parallel to the loading direction led to an increase in the maximum load bearing capacity of the composite. A more uniform hole distribution can enhance the overall mechanical performance of FRC. Furthermore, in the presence of thermal shock, crack propagation tends to grow towards the hole. These findings are of great significance for understanding the fracture behavior of FRC, and for optimizing material design and fabrication processes.